Transcriptional changes and the role of ONECUT1 in hPSC pancreatic differentiation - Sandra Heller (Nature Portfolio, 2021)
Heller et al analyze transcriptomic and epigenetic datasets from human PSCs differentiating into pancreatic progenitors to elucidate the regulatory mechanisms behind pancreatic development. The authors report that the transcription factor ONECUT1 is expressed specifically in pancreatic development and associates with other key TFs (such as FOXA2, GATA6, PDX1) during endocrine specification.